2004 International Conference on Communications, Circuits and Systems (IEEE Cat. No.04EX914) 2004
DOI: 10.1109/icccas.2004.1346128
|View full text |Cite
|
Sign up to set email alerts
|

A performance investigation of the modified PCF under hidden station problem

Abstract: Absfracf-A' modified version of the point coordination function (PCF) in the IEEE 802.11 standard called the Modified PCF has been introduced to improve the channel utilization over the standard PCF. The Modified PCF is a hybrid scheme incorporating polling and channel sensing. Therefore, a collision might occur in the channel if some stations cannot sense the change of channel status in case there is a station transmitting a packet, the so-called hidden station problem.In this paper, we present an investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The biggest disadvantage of PCF is that a lot of bandwidth is wasted by sending polls and NULL data when stations have no data to send. In order to reduce the overhead and increase the channel utilization, some works have investigated the performance of the PCF when used to support real-time traffic, and modified the standard PCF [4][5][6][7][8][9][10][11].These algorithms don't avoid unsuccessful polling. When a voice packet arrives, the station may transmit it in the next PCF.…”
Section: Related Workmentioning
confidence: 99%
“…The biggest disadvantage of PCF is that a lot of bandwidth is wasted by sending polls and NULL data when stations have no data to send. In order to reduce the overhead and increase the channel utilization, some works have investigated the performance of the PCF when used to support real-time traffic, and modified the standard PCF [4][5][6][7][8][9][10][11].These algorithms don't avoid unsuccessful polling. When a voice packet arrives, the station may transmit it in the next PCF.…”
Section: Related Workmentioning
confidence: 99%
“…The biggest disadvantage of PCF is that a lot of bandwidth is wasted by sending polls and NULL data when stations have no data to send. In order to reduce the overhead and increase the channel utilization, some works have investigated the performance of the PCF when used to support real-time traffic, and modified the standard PCF [4][5][6][7][8][9][10][11].…”
Section: Related Workmentioning
confidence: 99%
“…We have observed that there are very few works dealing with the PCF, which can indeed potentially achieve better performance than the DCF under heavy traffic conditions. Some contributions related to the PCF improve the overall network performance through novel scheduling algorithms [8]- [12] or by designing new polling mechanisms that can reduce the overhead associated to the polling process [13]. However, there have been almost no efforts in extending the operation of the PCF to ad hoc networks in order to provide them with some degree of QoS.…”
mentioning
confidence: 99%